The effects of an acute resistance exercise bout on appetite and energy intake in healthy older adults. (1st September 2021) - Johnson, Kelsie Olivia; Mistry, Nathan; Holliday, Adrian; Ispoglou, Theocharis
Abstract: Ageing is associated with reductions in appetite and food intake leading to unintentional weight loss. Such weight loss, particularly through muscle mass reduction, is associated with muscle weakness and functional decline, which represent predictors of poor health outcomes and contribute to frailty in older adults. Exercise-induced anorexia is an established phenomenon in young adults; however appetite and energy intake (EI) responses to resistance exercise are unknown in older adults. Twenty healthy older adults (68 ± 5 years, BMI 26.2 ± 4.5 kg m −2 ) undertook two 5-h experimental trials. Participants rested for 30 min before being provided with a standardised breakfast (196 kcal, 75.2% carbohydrate, 8.9% protein and 15.9% fat). Participants then rested for 1-h before completing: 1-h resistance exercise bout followed by 2-h of rest (RE) or, a control condition (CON) where participants rested for 3 h, in a randomised crossover design. Appetite perceptions were measured throughout both trials and on cessation, an ad libitum meal was provided to assess EI. A repeated-mesures ANOVA revealed no significant condition x time interaction for subjective appetite ( p  = 0.153). However, area under the curve for appetite was significantly lower in the RE compared with CON (49 ± 8 mm h −1 vs. 52 ± 9 mm h −1, p  = 0.007, d  = 0.27) . There was no difference in EI (RE = 681 ± 246 kcal; CON = 673 ± 235 kcal; p  = 0.865), suggesting that resistance exercise does not affect EI 2 h post-exercise in older adults despite a significant but modest reduction in appetite over a 5-h period. In conclusion, resistance exercise may be an appropriate means for optimising muscle mass adaptations without attenuating acute EI of older adults.